E4F1 COORDINATES PYRUVATE METABOLISM AND THE ACTIVITY OF THE ELONGATOR COMPLEX TO ENSURE TRANSLATION FIDELITY DURING BRAIN DEVELOPMENT - Michela, Di Michele; Aurore, Attina; Pierre-François, Roux; Imène, Tabet; Sophie, Laguesse; Javier, Florido; Morane, Houdeville; Armelle, Choquet; Betty, Encislai; Giuseppe, Arena; Carlo, De Blasio; Olivia, Wendling; et al. (Nature communications, 2024)
Pyruvate metabolism defects lead to severe neuropathies such as the Leigh syndrome (LS) but the molecular mechanisms underlying neuronal cell death remain poorly understood. Here, we unravel a connection between pyruvate metabolism and the regulation of the epitranscriptome that is relevant to LS pathogenesis. We identified the transcription factor E4F1 as a key coordinator of AcetylCoenzyme A (AcCoA) production by the pyruvate dehydrogenase complex (PDC) and its utilization as an essential co-factor by the Elongator complex to acetylate tRNAs at the wobble position uridine 34 (U34). E4F1-mediated direct transcriptional regulation of Dlat and Elp3, two genes encoding key subunits of the PDC and of the Elongator complex, respectively, ensured proper translation fidelity and cell survival in the central nervous system (CNS) during mouse embryonic development. Furthermore, analysis of PDH-deficient cells highlighted a crosstalk linking the PDC to ELP3 expression that is perturbed in LS patients.